2020
DOI: 10.1088/1755-1315/584/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of coastal communities on management of domestic wastewater in Ternate City, Indonesia

Abstract: Coastal area is a region that highly vulnerable to environmental degradation. One of the problems occurred in the coastal area in Ternate city is the number of solid and liquid household waste throws to the watershed or sea water. The different of geographical characteristics in Ternate is the focus of this study. The study took place in Kampung Makassar Timur Village that has people who have the house on the sea water and Sangadji village who live in the coastal area. This research aims to determine the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Grey water samples were collected at residential outlets (Jiawkok et al 2013;Suoth and Nazir 2016;Hafiza et al 2019) or wastewater treatment plant (WWTP) inlets (Astika and Zaman 2017;Marleni et al 2020). Mixed wastewater samples were collected at WWTP inlets except in three studies (Nagu and Lessy 2020;Al-Ajalin et al 2020;Ratnawati and Sugito 2021) where they were collected at residential outlets. Black water samples were collected at residential outlets (Hafiza et al 2019) and WWTP inlets (Rochmadi et al 2010).…”
Section: Domestic Wastewater Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grey water samples were collected at residential outlets (Jiawkok et al 2013;Suoth and Nazir 2016;Hafiza et al 2019) or wastewater treatment plant (WWTP) inlets (Astika and Zaman 2017;Marleni et al 2020). Mixed wastewater samples were collected at WWTP inlets except in three studies (Nagu and Lessy 2020;Al-Ajalin et al 2020;Ratnawati and Sugito 2021) where they were collected at residential outlets. Black water samples were collected at residential outlets (Hafiza et al 2019) and WWTP inlets (Rochmadi et al 2010).…”
Section: Domestic Wastewater Characteristicsmentioning
confidence: 99%
“…Numbers within parentheses indicate mean values. Single values indicate results from one studyMachdar et al 2014;Astika and Zaman 2017;Wijaya et al 2017;Rahmawati et al 2019; Yulistyorini et al 2019a, b;Nagu and Lessy 2020;Oktiawan et al 2021;Nur and Komala 2021;Ratnawati and Sugito 2021…”
mentioning
confidence: 96%
“…One study focused on the erosion rates in coastal areas of Jayapura City and found that both natural factors (such as wave energy and sediment supply) and human activities (such as sand mining and coastal infrastructure development) contribute to the erosion process [2,3,6,7,8]. Another study examined the hydrodynamic processes along the coast of Jayapura City, identifying the influence of tidal currents, wave actions, and river discharges on sediment dynamics and shoreline changes [9,10,11,12,13]. These studies also emphasized the importance of considering climate change in coastal management strategies, as rising sea levels and extreme weather events can exacerbate erosion and coastal vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three-bin system, industrial businesses and other companies within Makassar have implemented several other waste management initiatives to reduce their overall environmental impact. Businesses have become increasingly aware of long-term waste's impact on the environment and have adopted practices such as increased packaging and labelling efficiency, reduced landfill dumping, and improved waste collection methods (Nagu and Lessy, 2020;Ahmad et al, 2019). It also includes using zero-waste production methods, which aim to produce a product with maximum efficiency while reducing waste.…”
Section: Introductionmentioning
confidence: 99%